2007
DOI: 10.1262/jrd.18098
|View full text |Cite
|
Sign up to set email alerts
|

Successful Mouse Cloning of an Outbred Strain by Trichostatin A Treatment after Somatic Nuclear Transfer

Abstract: Abstract. Although the somatic cloning technique has been used for numerous applications and basic research of reprogramming in various species, extremely low success rates have plagued this technique for a decade. Further in mice, the "clonable" strains have been limited to mainly hybrid F1 strains such as B6D2F1. Recently, we established a new efficient cloning technique using trichostatin A (TSA) which leads to a 2-5 fold increase in success rates for mouse cloning of B6D2F1 cumulus cells. To further test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 26 publications
1
90
0
2
Order By: Relevance
“…Artificially improving the rDNA epigenetic status before or immediately after NT is another option. Recently, several histone deacetylase inhibitors were used to treat the NT embryos to achieve better clone efficiency (52)(53)(54)(55). The histone deacetylase inhibitor can increase the overall histone acetylation level of donor cell chromatins, then make the genes more reachable to maternal factors, therefore, promoting reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Artificially improving the rDNA epigenetic status before or immediately after NT is another option. Recently, several histone deacetylase inhibitors were used to treat the NT embryos to achieve better clone efficiency (52)(53)(54)(55). The histone deacetylase inhibitor can increase the overall histone acetylation level of donor cell chromatins, then make the genes more reachable to maternal factors, therefore, promoting reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, it is well known that the efficiency of SCNT procedures (Wakayama et al 2005, Kishigami et al 2007) and of ESC derivation (Kawase et al 1994, Suzuki et al 1999) is influenced by the genetic background. The observed efficiencies of ESC derivation from our control embryos are similar to those previously reported by Gong et al (2008) in the hybrid B6CBAF1 strain, which was 15.3% for parthenogenetic blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects, corroborated in miniature pig SCNT embryos (Miyoshi et al 2010), have recently been questioned by Ono et al (2010), who compared the effects of different HDACis on cloning BD129F1 mice. The discrepancy of results in the mouse species can be probably attributed to strain-specific differences, as not all HDACis are equally effective in all genetic backgrounds (Kishigami et al 2007, Van Thuan et al 2009). With regard to the IE procedure, although Gasparrini et al (2003) previously reported the production of a cloned mouse using cytoplasts prepared by IE, we were unable to obtain live offspring from the IE group.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of development to morula/blastocyst stage embryos using the nuclei from cells taken from most organs of the frozen mice was very low (Table 1 and Fig. S1c) and not as efficient as when using live cumulus or fibroblast cell nuclei (11)(12)(13). However, cloned embryos derived from brain tissue nuclei developed into morulae/blastocysts (39%) at a rate similar to or even better (Fig.…”
Section: Adaptation Of the Nuclear Transfer Technique For Frozen Deadmentioning
confidence: 95%